Wilhelm Meisters Wanderjahre $1 (BBand 2s - Goethe, Johann Wolfgang von, 1749-1832 (Salt Lake City, UT : Project Gutenberg, 2000)
"Wilhelm Meisters Wanderjahre $1 (BBand 2" by Johann Wolfgang von Goethe is a novel published in 1821, with a substantially revised edition in 1829. This sequel to "Wilhelm Meister's Apprenticeship" follows Wilhelm and his son Felix on their travels, bound by mysterious rules of renunciation. Through encounters with peculiar families, geological discoveries, trapped gates, and embedded stories, the novel weaves together novellas, letters, and aphorisms into an unconventional narrative structure that challenged traditional novel forms of its time. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Wilhelm_Meister%27s_Journeyman_Years
Release date is 2000-11-01
This etext was prepared by Michael Pullen
Keywords: Bildungsromans; Italy -- Fiction; Alps -- Fiction